Effects of reconnection downstream conditions on electron parallel acceleration during the merging start-up of a spherical tokamak. (4th July 2019) - Inomoto, M.; Ushiki, T.; Guo, X.; Sugawara, T.; Kondo, K.; Mihara, T.; Minami, Y.; Inai, Y.; Kaneko, H.; Yanai, R.; Takahata, Y.; Tanabe, H.; et al.
Abstract: The axial merging method is one of the candidates to provide a center-solenoid-free start-up of high-beta spherical tokamak (ST) plasma. Two initially formed STs merge through magnetic reconnection in the presence of the guide (toroidal) magnetic field, which is perpendicular to the reconnection (poloidal) magnetic field. During ST merging start-up, electrons are effectively accelerated near the reconnection point where the reconnection electric field is almost parallel to the magnetic field. In order to evaluate the effectivity of this acceleration process on electron heating, the temporal and spatial distributions of generated energetic electrons are observed by a soft x-ray fast imaging system equipped on the UTST device. The energetic electrons were generated not only in the vicinity of the reconnection point but transiently in the inboard-side downstream region until the static electric field by charge separation grew to cancel the reconnection electric field component parallel to the magnetic field line. Adequate control of the downstream condition could enhance the generation of energetic electrons and provide a more effective conversion from the released magnetic energy to electron energy.